Ultra-low rate dry etching conditions for fabricating normally-off field effect transistors on AlGaN/GaN heterostructures. (February 2018) - Kim, Zin-Sig; Lee, Hyung-Seok; Na, Jeho; Bae, Sung-Bum; Nam, Eunsoo; Lim, Jong-Won
Abstract: Enhancement-mode transistors with uniform turn-on threshold voltage (Vth ) can be achieved using low damage and low rate gate recess etching techniques. In this work, dry etching conditions for a AlGaN/GaN heterostructure with an ultra-low etching rate of 1.5 nm/min were demonstrated and we succeeded the possibility to achieve a low etch rate of an AlGaN/GaN heterostructure in a Cl2 /BCl3 plasma using inductively coupled plasma (ICP). The etching development was successfully implemented in the achievement of a normally-off GaN/AlGaN based transistor. The optimal recess depth was determined after fabrication of various devices with different recess depth values and with various dry etching conditions and after examining the performances of fabricated devices various conditions, and determining the dependence of recess time. The optimized etching condition resulted in low damage and smooth morphology of the etched AlGaN/GaN surfaces. Fine control of the depth of the gate region recess was achieved for the AlGaN/GaN heterostructure without any etch-stop layer, and validated for the fabrication of field effect transistors (FETs) using conventional processes. The fabricated normally-off Al2 O3 /AlGaN/GaN MOSFETs delivered a high positive Vth of +5.64 V with a low off-state leakage current of ∼10 −7 A/mm and lower current collapse.